2010
DOI: 10.21608/jppp.2010.86938
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TEMPERATURE AND RELATIVE HUMIDITY ON THE RATE OF DEVELOPMENT, FECUNDITY AND LIFE TABLE PARAMETERS OF THE RED SPIDER MITE Oligonychus mangiferus (RAHMAN AND, SAPRA) (ACARI: TETRANYCHIDAE)

Abstract: Studies on biology of Oligonychus mangiferus (Rahman and Sapra) at combination of eight constant temperatures and relative humidities (RHs) viz., 7.0°C with 85% RH, I0°C with 80% RH, 15.0°C with 75% RH, 23.0°C with 70% RH, 31.0°C with 65% RH, 34.0°C with 65% RH, 36.0°C with 60% RH and 40.0°C with 55% RH revealed that the optimal condition for the development of these mites are 15.0-31.0°C and 65-75% RH. The highest temperature and the lowest RH accelerated the rate of development and induced more reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The highest rm values of O. mangiferus in the present study and that of Ming-Ying Lin (2013) Fu and Zhang (2002) and Abou-Awad et al (2011) averaged 0.178, 0.182, 0.396 and 0.125, when the temperature was 31, 29, 28, 31 °C, respectively. On the other hand, Wrensch (1985) found that the highest rm values of various Tetranychus species ranged from 0.355 to 0.46.…”
Section: Ii: Reproduction and Life Table Parameters:-supporting
confidence: 40%
See 1 more Smart Citation
“…The highest rm values of O. mangiferus in the present study and that of Ming-Ying Lin (2013) Fu and Zhang (2002) and Abou-Awad et al (2011) averaged 0.178, 0.182, 0.396 and 0.125, when the temperature was 31, 29, 28, 31 °C, respectively. On the other hand, Wrensch (1985) found that the highest rm values of various Tetranychus species ranged from 0.355 to 0.46.…”
Section: Ii: Reproduction and Life Table Parameters:-supporting
confidence: 40%
“…Longevity period of spider mite decreases as increasing of temperature (Zaher and Shehata 1971;Fu and Zhang 2002;Abou-Awad et al 2011;Ming-Ying Lin 2013). The longevity of O. mangiferus recorded in this study resembles that of Zaher and Shehata (1971), Fu and Zhang (2002) and Ming-Ying Lin (2013) while Nangia et al (1989) and Abou-Awad et al (2011) found that O. mangiferus lived considerably longer. Table (3) showed that the net reproductive rate (R0) decreased when temperature increased.…”
Section: Ii: Reproduction and Life Table Parameters:-mentioning
confidence: 99%
“…. Highest fecundity of 46.43 eggs per female was registered at 31°C and 65% RH(Abou-Awad et al, 2011) Lin (2013). obtained highest daily fecundity at 29°C with 3.2 eggs per female.…”
mentioning
confidence: 82%
“…Based on these data, Lin (2013) estimated that O. mangiferus could complete 26 generations per year on mangoes in Taiwan. However, this figure dropped to 14-20 in Egypt on the same host (Zaher et al, 1982;Abou-Awad et al, 2011)…”
Section: Conclusion Of Pest Categorisation (Section 4)mentioning
confidence: 95%
See 1 more Smart Citation